Development and validation of a Rasch-Model-Based scale for assessing social skills in junior high school students: A study in Indonesia - Saputra, Randi; Hanurawan, Fattah; Muslihati, Muslihati; Akbar, Sadun; Alfaiz, Alfaiz (International Journal of Research in Counseling and Education, 2023)
This research focuses on the development and validation of a scale to measure the social skills of junior high school students in Indonesia. The study involved 420 students from various regions, utilizing a quantitative approach with a Likert rating questionnaire of four choices. The Rasch model was employed for analysis using Winsteps software. The item reliability index yielded a robust value of 0.80. Evaluation of item polarity across all aspects fell within the range of 0.12 to 0.78, while outfit-MNSQ values ranged from 0.12 to 1.90. Fourteen items were identified as unfit, failing to meet criteria due to Outfit MNSQ values > 1.5 and Pt Measure Correlation < 0.4, leading to their elimination. Additionally, two items with Outfit MNSQ > 1.5 were earmarked for editorial revision. The analysis revealed four items with nearly identical logit values, indicating redundancy in measurement. Consequently, one item from each pair was retained, simplifying the instrument. The study affirms the validity and reliability of the measurement instrument, indicating its suitability for assessing junior high school students' social skills.